Considerations for the preparation and conduct of international swimming teams - Rushall, B. S.
On how to prepare swimmers for international meets an the principles which primarily emphasize that there is a time well before an important competition when i) maximum fitness should be achieved so that no further "hard" training will produce any beneficial effect, ii) skill alterations should cease because there is no possibility of developing changes of sufficient conditioned strength that could be used in a stressful competition, and iii) psychological training and emphases increasingly become more important as the competition approaches. This latter feature requires coaches to become skilled at presenting activities and exercises to develop appropriate mind sets and degrees of focus that will allow efficient movement skills and highly tuned energy systems to be employed in the most appropriate manner in a competitive effort. Finely-tuned enhanced levels of performance rarely happen by chance. The technology is now available to elevate swimmers to these new levels so that they will have the satisfaction of performing their best when they are supposed to.